EXPRESS-ANALYSIS OF THE AGGLUTINANT AND BAR SANDS HUMIDITY - S. L. Rovin; M. V. Mamaeva; P. A. Kushel (Литьë и металлургия)
The different methods of laboratory express-analysis of humidity of aggiutinant sands are investigated. The method and device for control of humidity content of different aggiutinant sands on the level of microwave electromagnetic pulse consumption are presented.